No effect of a single remote voluntary contraction on performance in women soccer players - Gallegos, B. G.; Brown, L. E.; Coburn, J. W.; Galpin, A. J.; Gazas, V. L. (The Journal of Strength and Conditioning Research, 2013)
Remote voluntary contractions (RVCs) are defined as muscle contractions remote from, yet concurrent with, the prime mover. Previous studies suggest this phenomenon may produce an ergogenic effect on performance. Currently, little research has examined the effects of a single RVC on complex performance in women athletes. The purpose of this study was to examine the effect of RVC on kick velocity and throw-in velocity in women soccer players. Fourteen women with competitive soccer experience in the past 2 years participated. Subjects performed 3 maximal effort kicks and 3 maximal effort throw-ins with and without RVC. The RVC condition consisted of maximal jaw clenching on a mouth guard during the concentric phase of each kick and each throw-in. During the control condition (CON), subjects were instructed to keep their mouths open, and no mouth guards were used. Analyses demonstrated RVC had no effect on kick velocity (CON: 65.65 ± 8.38 km/hr, RVC: 66.90 ± 9.40 km/hr) or throw-in velocity (CON: 49.55 ± 5.65 km/hr, RVC: 49.31 ± 3.81 km/hr). In conclusion, RVC via jaw clenching does not appear to enhance or negate kick or throw-in velocity in women soccer players. Therefore, athletes and coaches may choose to use mouth guards as they see fit.